Description of dental caries in school-age children at HKBP elementary school, Padang Bulan, Medan, 2022 - Ginting, Amnita; Siallagan, Ance M; Silaban, Velita (International Journal on Health and Medical Sciences, 2023)
Dental caries or cavities is a disease of the hard tissues of the teeth (email, dentin, and cementum), which is caused by the activity of micro-organisms in fermentable carbohydrates. Dental caries is characterized by demineralization of the hard tissues of the teeth. The purpose of this study is to describe the incidence of dental caries in school-age children at HKBP Padang Bulan Medan Elementary School  2022. The type of research used is a descriptive research design. The sample in this study are 140 respondents. The sampling technique used is the Total Sampling technique. The results of the study on the incidence of dental caries in school-aged children at the Padang Bulan HKBP Elementary School 2022 showed that the respondents' dental caries is in the category of having dental caries as many as 78 students (55.7%). It is hoped that the results of this study will serve as educational motivational material on the prevention of dental caries and how to treat dental caries in school-age children.